Using goals to understand users : analytics for product managers (O'Reilly Media, 2018)
"Successful product managers use advanced goal setting and tracking techniques inside analytics systems like Google Analytics to best understand how users interact with their products and boost conversions. This course teaches these advanced techniques and is designed for the product manager with basic analytics experience. You'll review the methods for setting up and accessing goal reporting, move quickly past simple tasks like measuring the quantity of people who complete a particular task before diving deep into results-oriented techniques like goal segmenting, custom reporting, and high impact methods for integrating goals into UX analytics reports. To get the most out of the course, learners should first view the O'Reilly video series 'Using Analytics to Inform Product Design.'"--Resource description page